OPTIMASI PENENTUAN BACK PRESSURE DALAM METODE PEMBORAN MANAGED PRESSURE DRILLING JENIS CONSTANT BOTTOM HOLE PRESSURE - Mirza Zein, Joydi
Constant Bottom Hole Pressure is one of Managed Pressure drilling method, which is usually called CBHP. In CBHP drilling method, bottom hole pressure is maintained equal with formation pore pressure. The maintaining is done by adding Back Pressure through the annulus so the hydrostatic pressure will be same with hydrodynamic pressure. One of the implementation of CBHP is circulation stopping. Bottom hole pressure, which is equal to hydrodynamic pressure in the beginning, will decrease approaching hydrostatic pressure in circulating stopping process. Thus, additional pressure is necessary to increase bottom hole pressure so it equals to formation pore pressure. In order to execute this method, precision of additional pressure value is important to consider regards to narrow pressure window. Back Pressure determination affected by the amount of pressure loss occurred while drilling fluid circulation in process. The occurred pressure loss is the cause why the bottom hole pressure while circulating is higher than the bottom hole pressure while drilling fluid is in static condition. The value of pressure loss affected by the parameter of mechanical pressure loss while drilling fluid circulation is on the process. In other words, the amount of necessary back pressure is equal to frictional force while drilling mud is circulating in annulus converted to additional pressure. Determination of frictional force with high precision is the key of success in CBHP operation. Nowadays, CBHP operation has been done in many fields with narrow pressure window, but only pressure loss by frictional pressure loss caused by mud rheology that considered. Meanwhile, mechanical frictional force is also affected by other parameters such as drillpipe rotation, wellbore inclination, and cutting presence.